Seasonal Changes in the Elemental Composition of Five Valuable Fish Species (Sparidae) from Bozcaada, North Aegean Sea: A Health Risk and Nutritional Benefit Assessment - İlknur Yuvka; Ali Rıza Kosker; Mustafa Durmus; Yılmaz Ucar; Yesim Ozogul (Foods, 2025)
This study investigates the seasonal variations in the elemental composition of five economically valuable Sparidae fish species from Bozcaada, North Aegean: red seabream (Pagrus major), gilthead seabream (Sparus aurata), saddled seabream (Oblada melanura), white seabream (Diplodus sargus), and common dentex (Dentex dentex), with a focus on both essential minerals and toxic metals. Fish samples (n = 10 per species per season) were collected across four seasons, and their weights and lengths were recorded. The concentrations of elements such as calcium, potassium, magnesium, phosphorus, copper, iron, manganese, zinc, chromium, nickel, selenium, cadmium, and mercury were analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The elemental concentrations varied as follows: Ca (11,388.46–55,470.76), K (17,230.83–27,594.86), Mg (1436.02–2326.73), Na (1962.30–7847.41), P (13,112.11–15,516.57), Fe (107.61–282.00), Cu (36.44–59.13), Mn (6.19–19.87), Zn (98.67–256.26), Cr (4.54–11.96), Ni (6.33–13.89), Se (0.82–7.33), Cd (0.08–0.32), and Hg (0.08–1.50) mg/kg. Health risk assessments, including Estimated Weekly Intake (EWI), Target Hazard Quotient (THQ), and Cancer Risk (CR), were calculated for both adult and child consumers. The results showed that while the essential minerals remained within safe limits, seasonal variations in the concentrations of toxic metals could pose potential health risks, particularly with frequent consumption. This research provides valuable insights into balancing the nutritional benefits and safety of fish from Bozcaada, offering recommendations for informed consumption and public health policies aimed at optimizing benefits while minimizing risks.